Me käymme joulun viettohon - Anckar, Pia-Gunn; Eirola, Seppo; Enlund, Sixten; Halviala, Jouko; Helling, Lennart; Liukkonen, Riitta; Raitio-Eirola, Anne; Ruuttunen, Esa; Valjakka, Jorma (Fg Classics, 1987)
18 kappaletta.
Keywords: esitykset; valikoimat